Capacity to Organize and Manage Online Teaching of some Higher Education Institutions - Nguyễn Như Khương; Nguyễn Thanh Thủy; Nguyễn Văn Tuấn (Journal of Technical Education Science, 2024)
Online teaching is a form of teaching developed in the late 1990s with Internet and hypertext technology. Online teaching applications are centrally located on the education service provider's web server and can be accessed by learners [1]. Online teaching has been widely applied in educational institutions, especially higher education in developed countries. In Vietnam, it has been widely deployed recently. There have been a number of research projects on the management of online teaching in higher education institutions such as that of Tran Thi Lan Thu [2], and research on the organization of online teaching for teachers, but there has been no research topic Evaluation of the capacity to organize and manage online teaching of higher education institutions. This article clarifies the theoretical basis for the capacity to organize and manage online teaching of higher education institutions, thereby assessing the current situation of the capacity to organize and manage online teaching through a number of popular higher education institutions through survey methods using questionnaires and interviews with teachers and administrators. Research results have shown some limitations in the capacity to organize and manage online teaching of higher education institutions.